2020
DOI: 10.1111/jth.14671
|View full text |Cite
|
Sign up to set email alerts
|

The prevention and management of asparaginase‐related venous thromboembolism in adults: Guidance from the SSC on Hemostasis and Malignancy of the ISTH

Abstract: Venous thromboembolism is a common complication of asparaginase-based chemotherapy regimens for the treatment of acute lymphoblastic leukemia. Thrombosis associated with asparaginase administration poses a number of specific and often clinically challenging management decisions. This review provides guidance on the prevention and treatment of thrombosis associated with asparaginase in adults including discussions on antithrombin repletion, pharmacologic thromboprophylaxis, cerebral venous thrombosis, and thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
0
30
0
2
Order By: Relevance
“…For each of the topics, guidance statements were generated following review of published literature and are based on consensus opinion of the authors. Thrombotic complications applicable to acute leukemia have been addressed in previous SSC guidance documents that include the management of thrombosis in cancer patients with thrombocytopenia 1 and those associated with L‐asparaginase 2 …”
Section: Scope and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…For each of the topics, guidance statements were generated following review of published literature and are based on consensus opinion of the authors. Thrombotic complications applicable to acute leukemia have been addressed in previous SSC guidance documents that include the management of thrombosis in cancer patients with thrombocytopenia 1 and those associated with L‐asparaginase 2 …”
Section: Scope and Methodologymentioning
confidence: 99%
“…LMWH thromboprophylaxis was suggested throughout induction therapy with L-asparaginase in patients without severe thrombocytopenia (ie, platelet count <30 × 10 9 /L) or concern for hemorrhage. 2 Studies have consistently shown a reduction of fibrinogen levels with L-asparaginase treatment. 56,57 Hypofibrinogenemia can result in abnormal coagulation assays, but its effects on hemorrhagic or thrombotic outcomes are conflicting.…”
Section: Other Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the use of AT concentrates to prevent VTE in peg-asparaginase-treated patients is also controversial. The recently published International Society of Thrombosis and Hemostasis SSC (NC, USA) guidance document suggests monitoring of AT level as well as repletion during peg-asparaginase therapy in the adult population after the literature showed a 60% risk reduction in VTE when implementing such strategies [ 32 ]. Whether the AYA population can benefit from a similar approach warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%